Exploring Factors Shaping Dental Insurance Utilization: Insights from an Investigation in Iran: Dental Services Utilization Factors in Iran - Aryan Kya, Michael; Rojhanian, Tayebe; Sayar Irani, Fatemeh (Journal of Dental School, 2024)
Objectives One of the key indicators of the effectiveness of a country's healthcare system is the delivery of accessible and impactful health services, particularly in the field of oral and dental healthcare. Among the barriers to the utilization of oral and dental healthcare services within healthcare systems, the most prominent obstacles are a lack of awareness and insufficient financial resources. The objective of this research is to investigate the factors that influence the extent to which individuals in Iran make use of dental insurance services. Methods The research employed a linear probability model to evaluate how eight independent variables influence the utilization of dental insurance services. These variables included possession of supplementary dental insurance, age, parenthood, marital status, gender, level of education, DMFT index, and accessibility. The study encompassed data from 384 policyholders who participated across 20 dental clinics located in Tehran. Sampling was conducted using a stratified random sampling method, covering individuals with dental insurance from mid-2022 to mid-2023. The Kolmogorov-Smirnov test ensured data normality. One-sample examined hypotheses, while Pearson's Chi-Square tested relationships. The Gamma coefficient assessed relationship strength, and the Friedman test ranked factors influencing dental service utilization. Results Possessing supplementary dental insurance with an average rank of 5.2 is the most influential factor in the extent of utilization of dental services. The DMFT index, ranking on average at 2.5, is identified as the third factor (following accessibility to dental services as the second factor) in the utilization of dental services. Conclusion Possessing insurance emerges as a crucial factor compared to the DMFT index when it comes to dental visits. In other words, Iranians with a DMFT index but lacking insurance coverage show a lower likelihood of seeking dental treatment. This observation holds true even in the more affluent northern areas of Tehran, contrasting with regions spanning from center to lower Tehran.